Catalytic distillation : design and application of a catalytic distillation column - Nieuwoudt, Josias Jakobus (Jako) (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2005.